The personalized approach to choosing a contraceptive: weighing the pros and cons - Yu E Dobrokhotova; E I Borovkova (IP Berlin A.V., 2017)
The article presents the latest data on the risks of complications development on the background of the use of combined oral contraceptives, as well as the treatment effects of the use of hormonal contraceptives.